Modular Organization of the Thermobifida fusca Exoglucanase Cel6B Impacts Cellulose Hydrolysis and Designer Cellulosome Efficiency. Issue 10 (28th September 2017) - Setter‐Lamed, Eva; Moraïs, Sarah; Stern, Johanna; Lamed, Raphael; Bayer, Edward A.
Abstract : Cellulose deconstruction can be achieved by three distinct enzymatic paradigms: free enzymes, multifunctional enzymes, and self‐assembled, multi‐enzyme complexes (cellulosomes). To study their comparative efficiency, the simple and efficient cellulolytic system of the aerobic bacterium, Thermobifida fusca, is developed as an enzymatic model. In previous studies, most of its cellulases are successfully converted to the cellulosomal mode and exhibited high cellulolytic activities, except for Cel6B, a key exoglucanase of the T. fusca enzymatic system. Here, the impact of the modular organization of Cel6B on enzymatic activity is investigated. The position of the cellulose‐binding module (CBM), its family and linker segment are shown to affect activity. Surprisingly, exchange of the native family‐2 CBM to family‐3 generates an increase in Cel6B activity on cellulosic substrates. Conversion of Cel6B to the cellulosomal mode by fusing a cohesin to the catalytic module enables formation of divalent enzyme complexes with dockerin‐bearing enzymes. The resultant pseudo‐cellulosomes, containing Cel6B combined with endoglucanase Cel5A, exhibits enhanced enzymatic activity, compared to mixtures of wild‐type enzymes or bifunctional enzymes, unlike similar pseudo‐cellulosomes containing endoglucanase Cel6A or proccessive endoglucanase Cel9A. Insight into the different enzymatic paradigms benefits ongoing development of efficient cellulolytic systems for conversion of plant‐derived biomass into valuable sugars. Novelty statement: The protein engineering of the modular arrangement of a key exoglucanase from a highly cellulolytic bacterium, Thermobifida fusca, served to explore and compare three major enzymatic paradigms for cellulose degradation. This approach revealed highly active chimaeric forms of the exoglucanase that act in synergy together with a potent endoglucanase in bifunctional enzymes or divalent pseudo‐cellulosome‐like complexes. Such engineered enzymes could be further integrated into larger enzymatic complexes, thereby providing a significant step forward towards conversion of the entire T. fusca free cellulolytic system into the cellulosomal modex and the enhanced conversion of cellulosic biomass into soluble sugars. Abstract : By protein engineering, the modular architecture of free wild‐type enzymes and integrate cellulosomal elements (cohesin and dockerin modules) that are specifically binding to each other thus creating pseudo‐cellulosomes are modified. These enzymatic complexes serve as a basic tool for examining the benefits of the different enzymatic paradigms on cellulose degradation. The study contributes to the ongoing development of efficient cellulolytic systems for conversion of plant‐derived biomass into valuable sugars.